2021
DOI: 10.1073/pnas.2013230118
|View full text |Cite
|
Sign up to set email alerts
|

G-quadruplex structural variations in human genome associated with single-nucleotide variations and their impact on gene activity

Abstract: G-quadruplexes (G4s) formed by guanine-rich nucleic acids play a role in essential biological processes such as transcription and replication. Besides the >1.5 million putative G-4–forming sequences (PQSs), the human genome features >640 million single-nucleotide variations (SNVs), the most common type of genetic variation among people or populations. An SNV may alter a G4 structure when it falls within a PQS motif. To date, genome-wide PQS–SNV interactions and their impact have not been investigated. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 69 publications
4
40
0
Order By: Relevance
“…The single-molecule visualization of G4s revealed that dynamic G4 formation is associated with transcription, as G4 dynamics are disrupted by the inhibition of transcription [ 40 ]. The same conclusion was derived by a genome-wide interaction study between PQS and single nucleotide variation (SNV) and their impact on transcription [ 92 ]. SNV in PQS can impact the G4 structure, thereby resulting in G4 variation (G4V).…”
Section: G-quadruplexsupporting
confidence: 60%
See 1 more Smart Citation
“…The single-molecule visualization of G4s revealed that dynamic G4 formation is associated with transcription, as G4 dynamics are disrupted by the inhibition of transcription [ 40 ]. The same conclusion was derived by a genome-wide interaction study between PQS and single nucleotide variation (SNV) and their impact on transcription [ 92 ]. SNV in PQS can impact the G4 structure, thereby resulting in G4 variation (G4V).…”
Section: G-quadruplexsupporting
confidence: 60%
“…SNV in PQS can impact the G4 structure, thereby resulting in G4 variation (G4V). The majority of G4Vs overlap with gene regulatory elements, such as transcription factor (TF) binding sites and enhancers, and G4Vs in the regulatory regions have been reported to exhibit a significant influence on gene expression [ 92 ].…”
Section: G-quadruplexmentioning
confidence: 99%
“…Short genetic variants may cause the gain, loss, and/or change in folding propensity of G4s that modulate transcriptional gene expression (25). Therefore, it is a fundamental issue to address the physiological function and pathological implications that such short genetic variations may represent.…”
Section: Obtaining a Novel Dataset Of Disease-related G4-vars Within ...mentioning
confidence: 99%
“…G4 DNA is densely represented in function-specific genomic areas, such as promoters, promoter enhancement regions, oncogenes, and to a high degree, telomeres, all pointing to specific and important functional roles of the G4 structures [ 1 , 2 , 11 ]. Telomeres, G-rich single-stranded 3′ extensions at chromosome ends (TTAGGG) in the form of overhangs, are the most common region in which G4s form.…”
Section: G4 Dnamentioning
confidence: 99%